The Influence of School Context Factors on the Induction Support as Perceived by Newly Qualified Teachers - Van der Pers, Marieke; Helms-Lorenz, Michelle (Frontiers in Education, 2021)
This study explores the relationship between school demographic characteristics and the amount of provided induction activities, as perceived by beginning teachers (BTs), with special attention for Professional Development Schools and non-Professional Development Schools. The aim is to provide information that is useful to improve induction arrangements to particular school contexts. Data were collected in a Dutch national induction program in which qualified BTs are supported in their first three years of professional practice. The support monitor measures multiple induction activities with regard to the implementation of workload reduction, school enculturation, professional development plans and lessons support. 1,670 BTs working in 195 schools reported on these activities. Linear regression analyses revealed that less induction activities were associated with schools with multiple locations, more enrolled students and number of BTs employed, and with schools with older male teaching staff. No significant differences were found between the amount of support perceived by BTs in PDSs and non-PDSs. Yet school characteristics revealed stronger predictive values for the amount of support provided in non-PDS settings. These insights are relevant for mapping school differences in induction arrangements in order to enhance the equity of support across schools to assure the development of teaching skills of BTs.